Kompetensi Digital dalam Pedagogi Sains bagi Guru Pendidikan Agama Islam di Kota Palembang - Dadang; Jumhur; Karep; Dina Yuniati (Jurnal Penelitian Pendidikan IPA, 2025)
This study analyzes the efforts to improve the digital Science pedagogy competence of PAI teachers at MAN 3 Palembang City, which is increasingly important in the digital era. Teachers are required to integrate technology in learning innovatively. This research uses a qualitative approach with a case study method and data collection techniques through observation, interviews, and documentation to explore the efforts made in improving these competencies. The overall explanation of the digital pedagogical competence of PAI teachers at MAN 3 Palembang involves several important steps. Teachers have a positive attitude towards ICT, in-depth knowledge, and the ability to apply it in learning through technology such as video, multimedia, and online discussion. They are skilled in planning, implementing, and evaluating learning with ICT, and continue to develop themselves according to students' needs. In addition, teachers are able to integrate learning theories with students' characteristics, thus creating relevant, interesting and effective learning to achieve the desired learning objectives.